Forgiveness: A Key Component of Healing From Moral Injury? - Brémault-Phillips, Suzette; Cherwick, Terry; Smith-MacDonald, Lorraine Alison; Huh, John; Vermetten, Eric (Frontiers in Psychiatry, 2022)
Service members and veterans can be exposed to potentially traumatic and morally injurious experiences (PMIEs) including participating in, witnessing, or failing to prevent an act(s) that transgresses their core beliefs. Violation of one's deeply held morals and values can be profoundly distressing and shatter one's sense of self at the deepest level. Relationships with self, others, the world, and for some, the Sacred, can also be fractured. Post-Traumatic Stress Disorder (PTSD) and/or Moral Injury (MI) can result. Left unresolved, MI can leave individuals struggling with guilt, shame, cognitive dissonance, and negative self-attributions. A holistic approach that addresses the psychological and spiritual harm associated with MI is warranted. We wonder if forgiveness can help individuals struggling with MI to address the harm caused by actions or inactions, release negative emotions, and mend relationships. Commonly used by Spiritual/Religious (S/R) Leaders, forgiveness practices are increasingly being explored by Mental Health Professionals as a complement to evidence-based treatment approaches. This article provides case examples that illustrate the use of forgiveness practices that promote recovery and identifies programs used in clinical practice that incorporate forgiveness. Research is yet needed to better understand the importance of forgiveness in the treatment and healing of PTSD and/or MI. This requires an interdisciplinary discourse between Mental Health Professionals and S/R Leaders working in the field of MI. Such engagement and integrated use of forgiveness practices may yield improved outcomes not only for service members and veterans, but for all those struggling as a result of PTSD and/or MI.